PEMANFAATAN MULTIMEDIA DALAM PEMBELAJARAN BAHASA INGGRIS UNTUK PEROLEHAN BELAJAR NARRATIVE TEKS SISWA SMP - Askatriyani, Askatriyani; Sutapa, Y. Gatot; Mering, Aloysius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed at determining the utilization of multimedia in learning English for the learners. The use of multimedia should be able to fulfill the needs of the learners and can make the learners easy to understand the material being studied. This research used descriptive qualitative approach. Data collection techniques used were observation, interview, and documentation. The results of this research were (1) narrative text learning design using multimedia in SMP Negeri 14 Pontianak done by the teacher through preparing some of required aspects such as curriculum analysis, learning need analysis, method, appropriate evaluation and strategy for the learners, as well as the using of media, (2) the implementation of English learning using multimedia could be done well. It could be seen from the active learners in learning activities, (3) The learners’ attitude in achieving the acquisition of learning narrative text by utilizing multimedia based on observations was that learners became more interested and felt happy in learning activities, learners became more active and enthusiastic, and also the learners more excited doing the evaluation test by using multimedia. It can be concluded that the utilization of multimedia in learning English for the acquisition of learning narrative text class VIII students SMP Negeri 14 Pontianak ran well because it can make the learners interested as well as increased the learners' motivation so the learners became enthusiastic in the learning process.Keywords: The utilization of multimedia, learning english, acquisition of learning.